Interpretations of Generic Versus Comparative Statements About Groups: Similarities and Differences - Lux, Alexandra; Bruckmüller, Susanne; Hoorens, Vera (Journal of Language and Social Psychology, 2024)
We compare interpretations of two kinds of statements that are important for stereotype transmission: generics (e.g., “women are helpful”) and comparatives (e.g., “women are more helpful than men”). Participants (N = 338) read and interpreted generic or comparative statements about positive and negative features of gender (Experiment A) and age groups (Experiment B). We found similarities and differences. Participants interpreted both generics and comparatives as conveying information not only about the target (women in the example) but also about the referent (men in the example), whether the statement explicitly mentioned the referent (in comparatives) or not (in generics). When statements said something positive (negative) about the target, they also communicated a rather negative (positive) view of the referent. Remarkably, although comparatives explicitly contrast groups while generics do not, generics implied bigger differences between the groups and provoked more extreme assumptions about the groups. We discuss implications for stereotype transmission.
CRIS-Team Scopus Importer:2024-11-08
Keywords: fluency; focalism; impression formation; intergroup comparison; norms; stereotype transmission; verbal communication